Optimalisasi Konektivitas Antara Stasiun Cakung Dan Pasar Bintara - Telly - Rosdiyani (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
Bintara Market is a traditional market located in the village area of Bintara Bekasi City. Uniquely, this market is opposite Cakung Railway Station which is located in the Pulogebang Village area of East Jakarta, only 20 meters away. Visibly still looks chaotic arrangement of parking lots users park their vehicles carelessly so as to disrupt the trip. This study aims to find out how optimization of parking management is done, How much it costs to optimize parking management, What is the potential revenue levy after optimization and design a connectivity masterplan between Cakung Station and Bintara Market. The method used with data collection uses observation, field survey data records with supporting documentation as well as secondary data and literature. The results of the study obtained the addition of 850 motorcycle parking spaces and 250 SRP car parking, as well as potential parking revenue of Rp 3,860,000/day, the design of connectivity between the statsiun cakung -Bintara market and zebra cross so that the cost required for optimization of connectivity is Rp 2,159,036,425.